2012
DOI: 10.1007/s00268-012-1593-1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Quality Improvement in Low and Middle Income Countries of the Asia–Pacific Region: A Mixed Methods Study

Abstract: Our study provides the first description of trauma QI practices, gaps in existing practices, and barriers to QI in LMIC of the Asia-Pacific region. In this study we identified opportunities for addressing these challenges, and that work will be supported by APTQIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
(44 reference statements)
1
32
0
Order By: Relevance
“…Despite large differences in available resources, similar challenges appear to exist for trauma QI in low-and middleincome countries. For example, a recent workshop of stakeholders from 7 countries across the Asia-Pacific region convened at the Royal Australasian College of Surgeons identified a lack of integrated trauma QI activities, limited engagement of leaders, and the absence of standards of care as important gaps and barriers to effective trauma QI [21,22]. In response, the workshop participants (regional injury care champions) developed a QI network (Asia-Pacific Trauma Quality Improvement Network) to support local QI efforts by providing a forum for knowledge and experience exchange, increasing QI capacity through workshops and training, and coordinating the development and dissemination of trauma QI tools.…”
Section: Discussionmentioning
confidence: 98%
“…Despite large differences in available resources, similar challenges appear to exist for trauma QI in low-and middleincome countries. For example, a recent workshop of stakeholders from 7 countries across the Asia-Pacific region convened at the Royal Australasian College of Surgeons identified a lack of integrated trauma QI activities, limited engagement of leaders, and the absence of standards of care as important gaps and barriers to effective trauma QI [21,22]. In response, the workshop participants (regional injury care champions) developed a QI network (Asia-Pacific Trauma Quality Improvement Network) to support local QI efforts by providing a forum for knowledge and experience exchange, increasing QI capacity through workshops and training, and coordinating the development and dissemination of trauma QI tools.…”
Section: Discussionmentioning
confidence: 98%
“…a patient with a Glasgow Coma Scale <13 receives a head computed tomography scan within 2 hours of arrival; a patient with an abdominal injury and hypotension receives a laparotomy within 1 hour of arrival). 4, 5, 7 A study of trauma quality improvement programs in Asian-Pacific LMICs that included representatives from China, India, Malaysia, Philippines, Sri Lanka, Thailand, and Vietnam reported that no rural hospitals in these countries used audit filters to monitor and evaluate processes of trauma care. 4 Among the reasons for the lack of audit filter use at small hospitals proposed by the authors included a lack of standardized data collection mechanisms, limited resources (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3 Nonetheless, certain tools from trauma care quality improvement in HICs, such as prospective clinical audit, may be useful to LMICs working to reduce avertable death and disability due to injury. 4, 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the commencement of this Phase in July 2012, all three floors of the ETC were treating patients, including the ETU with co-located Radiology service on Ground Floor, the 4 Operating Theatres and Intensive Care Unit on First Floor, and the Short Stay Unit on Second Floor. Areas of focus for this phase included patient flow, admission protocols, managing all unexpected presentations, disaster planning, and quality improvement activities 14,15 .…”
Section: Methods -Program Deliverymentioning
confidence: 99%